(untitled) (Homoeopathy for All, 2025)
Homeopathy, a widely practiced alternative system of medicine, occupies a significant position in India’s healthcare and educational framework governed by the National Commission for Homoeopathy (NCH) under the Ministry of AYUSH. However, the homeopathic education sector faces persistent systemic challenges that undermine its quality, credibility, and potential for global integration. This article explores the major issues affecting homeopathic education from an expert standpoint. Addressing these multifaceted challenges is crucial to enhance the credibility, relevance, and future sustainability of homeopathic education in India